Studies on the care of the hospitalized client’s family: contributions to nursing - Valadares, Glaucia Valente; Paiva, Raquel Silva de (Rev Rene, 2010)
This is a bibliographic review which had the following aims: characterize the studies that focus on nursing care to the hospitalized client’s family, published from 2003 to 2008 and discuss the main diffi culties of the relationship nursing-family. For so, we used articles, thesis and dissertations available in the electronic online library: Scielo, data basis BIREME and LILACS as well as Capes, published from 2003 to 2008. The methodological approach chosen was a quanti-qualitative-analysis. The articles address the relationship between the nursing team and family members, emphasizing that this relationship is permeated by various confl icts. The article analysis showed that there are works turned to nursing and family however, there are still preliminary studies that map strategies like how the family can be a therapeutic tool in the hospitalization period.